Development of a SEM-EDS method for quantifying free mica in building materials - O'Connor, Leona (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2021)
The publication of Irish Standard IS 465:2018 highlighted the need for a technique to accurately and non-subjectively quantify free mica. The standard was developed to assist those who intend to provide assessment and testing services for dwellings that are suspected of being affected by defective concrete blocks. Utilising the latest technology in field emission scanning electron microscopy coupled with energy dispersive X-ray microanalysis (FE SEM-EDS), we developed and published a method during the course of this thesis, for forensically investigating and measuring excessive levels of deleterious materials in sand and in the hardened cement matrix of concrete blocks, testing which can be subjective or problematic using other methods. Our method requires the generation of high-resolution backscattered electron (BSE) images using the FE SEM, from highly polished samples, where the characteristic needle-like morphology of free mica can easily be identified. Additional information on the size, shape and chemical composition of the free mica fines, is gathered using energy dispersive spectroscopy (EDS or EDX). The combination of high-magnification images, high-resolution elemental maps, and mineral liberation software allows accurate identification and quantification of free mica within the sand fines and cement matrix. Thirty-two samples of building sands were independently collected from pits and builders suppliers around Ireland who know the provenance of the sand. Sub-samples of concrete blocks were extracted from two semi-detached dwellings in Co. Donegal, exhibiting the characteristic damage patterns from free mica or suspected of containing high concentrations of free mica. The sampling locations were the gable end, external leaf and internal leaf (standard 4 inch blocks used on their edge) and one of the big 12 load bearing blocks which are commonly used on their flat, at the base of the exterior foundation walls. Mica concentrations vary considerably in the sand samples tested. SEM-EDS analysis for the quantification of the percentage of free mica among the total fines gave the following results breakdown for the sand samples tested in seven samples it was <1.0 %, in a further fifteen it was between 1 5%, in five samples it was between 5 10% and four samples contained >10% mica. For the quantification of the same sand samples using XRD, the results correlated well with the SEM-EDS (R2 0.955), the mica concentrations also vary considerably in five samples it was not detected, in nine samples it was 0.3 1.0 %, in a further eight it was 1 5%, in five it was 5 10% and five samples contained >10% mica. Methylene blue comparative testing of the sand samples demonstrated poor correlation (R2 0.096) with all of the sand tested ≦1g / kg. The inhomogeneous nature of concrete blocks is a more complicated matrix to analyse, averaging twelve of more fields of view at 1200x magnification we were able to quantify the percentage of free mica among both the total fines and the cement matrix in the fields of view tested. The size of the area tested by SEM-EDS is small relative to the concrete block area, but the result demonstrates a quantitative value for the analysed areas.
APPROVED
Keywords: SEM-EDS; Concrete; free mica